2016
DOI: 10.4103/0971-3026.178367
|View full text |Cite
|
Sign up to set email alerts
|

Is TIRADS a practical and accurate system for use in daily clinical practice?

Abstract: Aim:To assess the positive predictive value (PPV) and inter-observer agreement of Thyroid Imaging Reporting and Data System (TIRADS) as described by Kwak et al.Materials and Methods:This was a prospective study wherein ultrasound was performed by two radiologists on patients with thyroid nodules >1 cm. The third radiologist interpreted archived images. Ultrasound features and TIRADS category were compared with cytology and surgical histopathology. PPV was calculated for all readers’ combined assessment. Inter-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
3
27
1
Order By: Relevance
“…Previous studies have demonstrated that TIRADS classification systems have good interobserver variability . However, some suggest that intermediate categories have poor interobserver variabilities compared to categories at the extremes of the spectrum . To the best of the authors’ knowledge, this study represents the first investigation in the literature evaluating interobserver variability among TIRADS classification in patients with cytologically indeterminate, Afirma suspicious thyroid nodules.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have demonstrated that TIRADS classification systems have good interobserver variability . However, some suggest that intermediate categories have poor interobserver variabilities compared to categories at the extremes of the spectrum . To the best of the authors’ knowledge, this study represents the first investigation in the literature evaluating interobserver variability among TIRADS classification in patients with cytologically indeterminate, Afirma suspicious thyroid nodules.…”
Section: Discussionmentioning
confidence: 89%
“…The aim of TIRADS was to decrease variation in the reporting of thyroid nodules and thereby improve patient management and cost‐effectiveness by minimizing the number of unnecessary FNAs. Previous studies have demonstrated that TIRADS classification systems have good interobserver variability . However, some suggest that intermediate categories have poor interobserver variabilities compared to categories at the extremes of the spectrum .…”
Section: Discussionmentioning
confidence: 99%
“…TIRADS is a simple, accurate, everyday applicable reporting system that provides stratification of thyroid nodules according to malignancy risk based on the number of suspicious US features. 7,29,30 It supplies categorization of a thyroid nodule according to the predicted malignancy risk. 7,8 Until now, various versions of TIRADS systems have been suggested for thyroid nodules.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have recently attempted to validate this type of approach as an instrument for use in clinical practice, with some authors proposing different TI-RADS versions in selected populations (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%